Constructing a language : a usage-based theory of language acquisition - Tomasello, Michael (Harvard University Press, 2003)
The author presents a comprehensive usage-based theory of language acquisition, based on evidence that children possess a linguistic ability interwoven with other cognitive abilities, rather than a self-contained 'language instinct'.